Feasibility of bacterial-enzyme induced carbonate precipitation technology for stabilizing fine-grained slope soils - Gowthaman, Sivakumar; Iki, Takashi; Ichinohe, Aoi; Nakashima, Kazunori; Kawasaki, Satoru (Frontiers in Built Environment, 2022)
Microbial Induced Carbonate Precipitation (MICP) has recently become a new technology for stabilizing the slope surface. The applicability of MICP, however, is limited in fine-grained soils due to the restrictions regarding the transportation of bacteria cells. The purpose of this study was to assess the feasibility of an alternative called Bacterial-Enzyme Induced Carbonate Precipitation (B-EICP) for stabilizing the fine-grained slope soils. Unlike the MICP strategy (involving whole-cells of bacteria), the proposed B-EICP utilizes bacterial urease to induce the bio-cement formation within soil. The whole-cell culture of Lysinibacillus xylanilyticus was subjected to cyclic sonication to extract the free urease suspension. The B-EICP treatment was performed to the columns prepared using two different soils obtained from representative expressway slopes. The cementation responses of the proposed B-EICP were compared with that of typical MICP method, especially from the following viewpoints, (i) adaptability to soil with high fine-grained content, (ii) conditions under which B-EICP can be effectively applied and (iii) cementation under low temperature. The results revealed that the extract solution had higher urease activity compared to original bacteria culture, and the activity remained more stable at low temperature conditions (15C). The results further confirmed that B-EICP method is more suitable for stabilizing soils with large amount of fine particles. Comparing with MICP, the B-EICP resulted higher unconfined compressive strength (over 1200 kPa) and deeper cementation in the silty sand. Microscale analysis suggested that the B-EICP could induce smaller calcium carbonate crystals than that by MICP, but the number of crystals in B-EICP were significantly more, thus contributed to increased particle-particle cementation.